A SWOT Analysis on Business Development of Perumda Barinas to Optimize Regional Original Income and the Community Economy - Jalaluddin; Rahmania, Nurul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Regional Public Companies (Perumda) have a strategic role in supporting regional original income and community economic development. One of the Perumda operating in West Sumbawa Regency (KSB) is Perumda Bariri Aneka Usaha (Barinas). Perumda Barinas KSB is experiencing a multidimensional crisis characterized by directors never completing their terms of office, the absence of a standard corporate organizational structure, non-functioning management systems, and the lack of Good Corporate Governance (GCG) implementation. This study aims to analyze the internal-external conditions, determine the strategic position, and formulate development strategies for Perumda Barinas. A qualitative approach with a case study method was employed through in-depth interviews with 12 informants (local government officials, former directors, supervisory board members, employees, and partners) and SWOT weighting questionnaires distributed to 15 respondents. The identification results revealed three strengths (full regional ownership, substantial assets, broad business scope) and nine dominant weaknesses (leadership crisis, absence of a standard structure, GCG not yet implemented). External factors include five opportunities (natural resource potential, workforce, industrial zone-smelter, presence of private companies, population growth) and three threats (negative stigma, unhealthy competition, political dynamics). The SWOT analysis yielded an IFAS score of -0.41 and an EFAS score of 0.63, placing Perumda Barinas in Quadrant IV (Turnaround Strategy). The strategies are formulated in three stages: short-term (0-6 months) stabilization through the recruitment of definitive directors and a forensic audit; medium-term (6-18 months) GCG implementation and strategic partnerships; long-term (18-36 months) business expansion in logistics and agriculture. The practical implication is that the Regional Government needs to immediately undertake organizational restructuring and capital injection. The research is limited to a single case study where the SWOT weights depend on the perceptions of the informants.